Frequency of Vitamin B12 Deficiency Anemia in Diabetic Patients on Metformin in a Tertiary Care Hospital, Lahore, Pakistan - Syed Zain Ul Abideen; Shafqat, Waseem; Mustafa, Farhan (Indus Journal of Bioscience Research, 2025)
Objective: To determine the frequency of vitamin B12 deficiency in patients with type 2 diabetes mellitus receiving metformin at a tertiary care hospital in Lahore, Pakistan, and to assess its association with age, gender, duration of diabetes, duration of metformin use, and body mass index. Methodology: This cross-sectional study was conducted in the Outpatient Department of Internal Medicine, Gulab Devi Hospital, Lahore, over six months (December 2024 to May 2025). A total of 150 patients aged 18–70 years with type 2 diabetes mellitus on metformin monotherapy for at least six months were included through non-probability consecutive sampling. Pregnant and lactating women, vegans, and patients with diagnosed diabetic peripheral neuropathy were excluded. Serum vitamin B12 level was measured in all participants, and deficiency was defined as a level below 150 pg/ml. Data were analyzed using SPSS version 25. Quantitative variables were expressed as mean ± standard deviation, while categorical variables were presented as frequency and percentage. Independent samples t-test and chi-square test were applied, and p-value